Donor Selection in Flow Replacement Bypass Surgery for Cerebral Aneurysms: Quantitative Analysis of Long-term Native Donor Flow Sufficiency. Issue 3 (27th October 2015) - Rustemi, Oriela; Amin-Hanjani, Sepideh; Shakur, Sophia F.; Du, Xinjian; Charbel, Fady T.
Abstract: BACKGROUND: Graft selection in extracranial-intracranial bypass surgery for cerebral aneurysms has traditionally been based on clinical impression and operator preference. However, decision making can be optimized with a donor selection algorithm based on intraoperative flow data. OBJECTIVE: To present long-term follow-up and quantitative assessment of flow sufficiency for native donors selected in this manner. METHODS: Patients with bypass for anterior circulation intracranial aneurysms using only a native donor (superficial temporal artery) selected on the basis of an intraoperative flow algorithm over a 10-year period were retrospectively studied. Intracranial hemispheric and bypass flows were assessed preoperatively and postoperatively when available with quantitative magnetic resonance angiography. RESULTS: Twenty-two patients with flow data were included (median aneurysm size, 22 mm). The intraoperative flow offer (cut flow) of the superficial temporal artery was sufficient in these cases relative to the flow demand in the sacrificed vessel (59 vs 28 mL/min) to warrant its use. Bypass flow averaged 81 mL/min postoperatively (n = 19). Bypass flows were highest in the immediate postoperative period but remained stable between the intermediate and final follow-up (40 vs 52 mL/min; P = .39; n = 8). Mean ipsilateral hemisphere flows were maintained after bypass (299 vs 335 mL/min; P = .42; n = 7), and remained stable over intermediate and long-term follow-up. Ipsilateral hemispheric flows remained similar to contralateral flows at all time points. CONCLUSION: Despite a relative reduction in bypass flow over time, hemispheric flows were maintained, indicating that simple native donors can carry sufficient flow for territory demand long term when an intraoperative flow-based algorithm is used for donor selection.